Amine‐modified poly(vinyl alcohol) as a novel surfactant to modulate size and surface charge of poly(lactide‐co‐glycolide) nanoparticles. Issue 7 (3rd May 2016) - Cella, Claudia; Martello, Federico; Ghisletti, Serena; Lenardi, Cristina; Milani, Paolo; Argentiere, Simona
Abstract : In emulsion‐based synthesis of poly(lactide‐ co ‐glycolide) nanoparticles, different mixtures of poly(vinyl alcohol) (PVA) and a novel surfactant (amino‐PVA) were investigated to obtain cytocompatible nanoparticles with good degradability, tunable size and endosomal escape potential. Abstract: Poly(lactide‐ co ‐glycolide) (PLGA) nanoparticles (NPs) represent a promising tool for effective delivery of biomacromolecules, thanks to their biodegradability and biocompatibility properties. PLGA NPs are often synthesized by the emulsion‐solvent evaporation method and poly(vinyl alcohol) (PVA) represents one of the most commonly used surfactants. Although PVA‐mediated synthesis of PLGA NPs is effective in tailoring NP size and stability, the resulting negative surface charge can prevent both endosomal escape and biomacromolecule release in cell cytosol. To overcome this limit, a novel amino‐modified PVA (amino‐PVA) surfactant with a cationic charge was synthesized and its potential for the formulation of PLGA NPs was investigated. In either single (oil‐in‐water) or double (water‐in‐oil‐in‐water) emulsion synthesis, different mixtures of PVA and amino‐PVA were studied, by monitoring their effects on NP size and surface charge. Optimized properties were obtained with a combination of 0.975% (w/v) of PVA with 0.025% (w/v) of amino‐PVA. This formulation was further investigated for degradation properties and cytocompatibility. High stability and low cytotoxicity make the system promising for the encapsulation and release of hydrophilic drugs and biomacromolecules. © 2016 Society of Chemical Industry